PENGARUH KECERDASAN EMOSIONAL DALAM MEMBENTUK AKHLAK SISWA SDN JAGABAYA 01 PARUNGPANJANG BOGOR - intan shurur; Eka Naelia Rahmah (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2024)
This research stems from a lack of understanding regarding emotional intelligence and the decline in students' morals. In emotional intelligence there are things related to emotions that can be an effort to shape students' morals. The aim of this research is to determine emotional intelligence in shaping student morals at SDN Jagabaya 01 Parungpanjang Bogor. This research is descriptive qualitative research where data collection uses observation methods, interviews with informants and documentation. The data analysis technique was carried out by collecting data, presenting data and drawing conclusions. The first method available in the area. In this research, there were informants who were used as primary data by the author, namely: Principal of SDN Jagabaya 01 Parungpanjang Bogor, PAI Teacher of SDN Jagabaya 01 Parungpanjang Bogor, Class V students and students of SDN Jagabaya 01 Parungpanjang Bogor The results of this research show that emotional intelligence in shaping the morals of class V students at SDN Jagabaya 01 Parungpanjang runs well and effectively, this is expressed by students who can recognize their own emotions, manage their emotions, motivate themselves, empathize, socialize, have morals towards Allah, humans, and the environment. There are efforts to shape student morals through several processes, namely politeness, helping each other, protecting the environment. Emotional intelligence can shape students' morals, this is expressed by students implementing good morals or behavior in the school environment and outside the school environment.